De novo LAMP2 insertion mutation causes cardiac-only Danon disease: A case report - Wang, James Jiqi; Yu, Bo; Song, Xiuli; Wang, Hong (Frontiers in Cardiovascular Medicine, 2022)
Danon disease is a rare disease caused by glycogen storage lysosomal disorder. It is related to pathogenic mutation of LAMP2 gene. Herein we present a patient with a novel pathogenic mutation (c.764_765insGA) with cardiac-only symptoms. Her family members don’t carry the same mutation she does, suggesting this is a de novo mutation. Further tests revealed vacuoles and glycogen disposition in patient’s heart tissue and significant decrease of LAMP2 protein expression. Protein structure remodeling of LAMP2 predicted that the mutant protein have conformational change lacking important transmembrane domain, subsequently causing protein destabilization.